Odpowiedź:
3d. 3b - 2a + ab = 3×7 - 2×6 + 6×7 =
3 × 7 = 21
2 × 6 = 12
6 × 7 = 42
21 - 12 + 42 = 51
3e. b² - 5a + ½a = 7² - 5×6 + 0,5×6 =
7² = 49
5 × 6 = 30
0,5 × 6 = 3
49 - 30 + 3 = 22
3f. 6(4a + 2b³) = 6(4x6 + 2x7³) =
4 × 6 = 24
7³ = 343
24 + 343 = 367
6 × 367 = 2202
4c. 19y + 14 = 20
20 - 14 = 6
19 × y = 6
6 ÷ 19 = 0,315789
y = 0,315789
4d. 7w - 15 = 12
12 + 15 = 27
7 × w = 27
27 ÷ 7 = 3,857
w = 3,857
5. 5(2x + 4) = 200
200 ÷ 5 = 40
2x + 4 = 40
40 - 4 = 36
36 ÷ 2 = 18
x = 18
Szczegółowe wyjaśnienie: